‘Mina’ de quantificadores: uma abordagem funcionalista - CARNEIRO, Elaine do Rêgo (2025)
This article is a final course work, developed at the Amazon Center for Semantic Studies of Portuguese (NAESP). In this sense, a discussion is proposed about the phenomenon of quantification, directing the focus to a non-canonical expression in Portuguese, used in some regions of the country, namely: mina. The aim of the work is to signal the process of linguistic change that occurs within the language, from the perspective of grammar motivation. For this reason, this study is anchored in the theories and postulastes of Functional Linguistics, in the studies of Rios de Oliveira (2020), Cunha et al (2015), in addition to the scholars Ferrarezi Jr (2008) and Cançado (2008). To carry out the research and analysis of the phenomenon in question, screenshots of conversations and posts on the WhatsApp, Instagram and Facebook apps were used, in which occurrences such as “Tão prendendo mina de gente” (“They’re arresting a lot of people”), among others, were found. The aforementioned research began on 11/17/2022 and ended on 03/04/2024 and seeks to contribute to grammatical studies of Brazilian Portuguese.